Acceso al agua y ciudadanía urbana en Lima, Perú: dinámicas hidrosociales e infraestructuras autogestionadas en asentamientos humanos - Zanella, Alhelí (2025)
Providing water to the city of Lima, which currently spans desert areas and is home to over 10 million inhabitants, represents an ongoing challenge for Lima’s public water and sewage company, SEDAPAL. Despite efforts to expand service coverage over the past 20 years, there are still households not connected to the water network, particularly in informal settlements. Given SEDAPAL’s limitations in achieving universal coverage, residents of informal settlements rely on self-built infrastructure to improve their water access, demonstrating a form of grassroots resilience and agency. This article explores the interaction between access to water, self-built infrastructure, and urban citizenship, focusing on the case of one informal settlement in the district of San Juan de Lurigancho. Through the hydro-social cycle concept, this article analyzes how residents have developed resilience strategies through self-managed infrastructure and informal agreements in the absence of official household connections. Drawing on the concept of citizenship as a contested and relational process, the research argues that access to water in informal settlements transcends the provision of a public service; it becomes a symbol of belonging, recognition, and inclusion within urban space.